Penyuluhan Pendirian Koperasi Sebagai Upaya Memasyarakatkan Koperasi pada mahaswaa Gen Z - Agustiani, Eka; Astuti, Endang; Pusparini , Herlina; p, Bambang (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2024)
The lack of understanding of the establishment and benefits of cooperatives among students (Gen z) underlies the implementation of this service activity. The purpose of this activity is to provide understanding and knowledge to students related to cooperatives, namely the procedure for managing cooperative establishment permits, strategic issues in cooperatives with the use of the OSS and KBLI systems, independence and reform in cooperatives and MSMEs, opportunities and problems for cooperative development among students. To achieve this goal, the solution is carried out in two ways, namely providing understanding and knowledge about the stages of managing cooperative establishment permits and several aspects of opportunities that are part of cooperative activities through counseling activities using the lecture method and providing direct examples to students who want to develop cooperatives. The counseling activity has gone well which was attended by around 19 students (Gen z) who took cooperative and MSME courses at Gegutu Reban Dasan Geria.